Where is the fracture? Penetrating injury with a foreign bone - Mahmut Kalem; Niyazi Ercan (Acta Orthopaedica et Traumatologica Turcica, 2018)
Injuries in the explosion scenarios are usually hollow organ injuries including rapid gas expansion, thermal injuries, penetrating injuries due to secondary projectiles and secondary injuries like falls and burns. Our case is a penetrating injury that was considered open knee fracture (Gustilo Anderson Type 3A) and peroneal nerve palsy in the emergency service after bomb attack but later it was seen that the secondary projectile was a foreign bone and the patient's bone integrity was intact. Our aim is to show that specific human tissues must be considered as a factor in the secondary injuries. Keywords: Foreign bodies, Blast injuries, Peroneal nerve palsy, Terrorist attack, Fracture